The Students' and Teachers' Voice During Pandemic Learning - Sianna Sianna; Ali Wira Rahman; Zubaidah B.A. Rasyid (Musamus Journal of Language and Literature, 2022)
A worldwide issue, the Covid-19 pandemic has affected practically every nation. Of course, it created turmoil when it emerged, and this included the education system. Learning that was formerly conducted in-person in classrooms is now done online and may be accessible from home. Although the system transition is thought to be able to enable learning throughout the pandemic, it really causes a number of problems for the community and even people who are engaged in the learning. The purpose of this study is to ascertain the opinions, worries, and preferences of students and teachers on the implementation of learning during the pandemic. The part that parents play in their children's education will also be examined in this study. The case study approach of qualitative research is used in this study. Participants in the study included 5 parents, 8 students, and an English teachers from SMP Negeri 10 Batu Satap. Additionally, semi-structured interviews were undertaken to gather the research data. The study's findings suggest that the pandemic's learning did not yet achieve its full potential for application. The implementation of the appropriate learning system by teachers and students is hindered by a number of issues, including network connectivity, the cost of meeting internet quotas, and issues specific to each student, such as trouble comprehending the subject matter and erratic study schedules. Parents of students are also involved in their children's education, but they are constrained in how much they can help because of their inadequate understanding.